Teaching Simple Present in Writing Through Short Story on Youtube To Accounting Students at University of Bina Sarana Informatika - Paramita Kusumawardhani (Scope : Journal of English Language Teaching, 2021)
This research discusses the use of short story on YouTube in teaching simple present tense to Accounting students. The development of technology has influenced in English teaching learning ways. There are some skills that should be mastered by the learners in learning English, they are listening, speaking, reading and writing. Technology can be used in all English skills, such as the use of YouTube in teaching writing. There are many short stories on YouTube that can be used as one of the media in teaching writing. Simple present is used to show the activity which is done repeatedly. It is also used to show about general truth or fact. It is chosen as the students, especially Accounting students, still have difficulties in implementing simple present in the sentence. The method used in this research was descriptive qualitative method and the participants of this research were the students from Accounting Department, 1st semester of University Bina Sarana Informatika. The results of the research are: (1) most students have understood about the pattern of the verb used in simple present tense; (2) most of them have known about using verbs or auxiliary verbs; and (3) some of them made mistakes of the writing of the verb and auxiliary verb.